STRATEGI PEMASARAN PRODUK KEMASAN MELALUI SALURAN DISTRIBUSI DAN KUALITAS PELAYANAN TERHADAPTINGKAT KEPUASAN KONSUMEN PADA PT. INDOGRAVURE DI CIPUTAT TANGERANG SELATAN - Deni Indra Purnama Koto (Equilibrium Point : Jurnal Manajemen dan Bisnis, 2019)
Strategy Marketing is tip of lance a company and very support and also fluent process the make-up of tidiness product sales revenue. professional and good Service quality a[n network to realize level satisfaction of his consumer. Satisfaction of consumer is mirroring of efficacy of company in marketing tidiness product which have been yielded by him. As for intention of this research is to know by together what is there is influence of Channel Distribution variable (X1) and Quality service (X2) to variable Satisfaction of Consumer (Y) at PT. Indogravure in Ciputat Tangerang South.Technique intake of sampel in this research is conducted with Random Sampling that is way intake of sampel at random regardless of existing strata in sampel. Where every population member have is same opportunity to be selected as sampel.Result Channel Distribution variable correlation analysis (X1) to Satisfaction of Consumer (Y) expressed there is positive influence with value equal to 0,917 or 84,1%, this matter there is very strong influence. This matter need in proving with hypothesis test between Channel Distribution variable (X1) to Satisfaction of Consumer (Y) obtained by value of to = 4,693 t0,05 (70) = 1,669, hence Ho refused and Is ha accepted, meaning there is influence isn't it. So also variable of[is Quality of Service (X2) to Satisfaction of Consumer (Y) expressed there is obtained by positive influence of value equal to 0,944 arau 89,1%, this matter show there is very strong influence, this matter isn't it with hypothesis test obtained by value test to = 8,001 t0,05 (70) = 1,669, hence Ho refused and Is ha accepted can be expressed there is influence isn't it. y together there is very strong and positive influence between Channel Distribution variable (X1) and Quality Service (X2) to Satisfaction of Consumer (Y) obtained by correlation value (R) equal to 0,958 and R Square 0,917 or the influence level of equal to 91,7%. This matter require to be proved with test of FCount obtained by value equal to 381,303 where the value bigger than Ftable with df = 71 and value of Ftable equal to 2,740 with level isn't it equal to 0,000 because 0,000 0,05, hence can be told by together Channel Distribution variable (X1) and Quality Service (X2) to Satisfaction of Consumer (Y) have an effect on isn't it.